How do they know what they know? The case of eyewitnesses - Sauerland, Melanie; Justus Liebig University Giessen (My University, 2007)
This dissertation reports 4 Experiments that are concerned with the evaluation of eyewitness identification testimony. In Experiment 1, three target description groups were assessed in order to test different theoretical accounts regarding the relationship between identification performance and target description (verbal overshadowing): non-describers, describers, and rereaders (describers with rereading of the description before the identification task). Rereaders less frequently chose somebody from the lineup than the other two groups, lending support to the decision criterion shift approach (Clare & Lewandowsky, 2004). In Experiment 2, post-decision confidence, decision time, and self-reported decision processes were used as postdictors of identification accuracy. Using a decision rule including highly confident and fast choosers led to more correct classifications than either variable alone. Unexpectedly, self-reported decision processes were neither associated with identification accuracy for choosers nor for nonchoosers. In Experiment 3, combinations of post-decision confidence, decision time, and Remember-Know-Familiar (RKF) judgments were evaluated as postdictors of identification accuracy in a field experiment with ten targets and a very large sample. Fast and confident choosers were highly accurate. Including the RKF judgment did not lead to higher correct classification rates. Participants' self-reported (estimated) decision times also proved to be a postdictor of identification accuracy. Postdicting nonchoosers' identification performance by forming three homogeneous groups of nonchoosers failed, although there were differences with regard to confidence measures and decision times. Experiment 4 tested the usefulness of multiple lineup decisions (portrait face, body, bag, and profile face) for the assessment of identification testimony for nine different targets. Performance in the four different lineup types was not associated with each other, lending support to the idea that multiple lineups can serve as independent sources of evidence. Compared to foil choices and lineup rejections, target/suspect choices were most diagnostic of guilt. The portrait face lineup alone and its combination with the body lineup were most diagnostic for target/suspect choices. To conclude, the present studies suggest that both decision times and post-decision confidence should be collected at the time of identification and be combined in order to assess identification accuracy. Investigators need to be aware though, that there is no postdictive value of nonchooser's estimates. Furthermore, there seem to be no negative effects of target descriptions on identification accuracy when there is a sufficient interval between description and identification, as there is in real cases. Finally, the data speak for the application of multiple lineups with regard to suspect/target choices as a procedure to avoid false identifications, whereas the benefit of multiple lineups for lineup rejections and foil choices seems to be limited. Future studies should address how many and which specific lineup types should be used. In real cases, the results for the assessment (decision times, confidence, decision processes) and control variables (target description, multiple lineups) examined in the present dissertation may vary from those that we obtain in laboratory or field studies. Reasons could be, for example, awareness of the severe consequences of false identifications and false rejections or the stress level at encoding or recognition. It would be interesting to collect data on these issues in real cases so they can be compared to the data obtained in laboratory/field studies. Undoubtedly, it would be a great contribution to the field of identification if data were collected even where DNA samples exist, so that identification accuracy could actually be assessed in real cases.

Die vorliegende Dissertation umfasst vier Experimente, die sich mit der Evaluation von Identifizierungsaussagen befasst. In Experiment 1 wurden drei Beschreibungsgruppen getestet, um theoretische Erklärungsansätze zum Zusammenhang zwischen Identifizierungsleistung und Personenbeschreibungen (verbaler Überlagerungseffekt) zu überprüfen: nicht-Beschreiber, Beschreiber und Wiederleser (Beschreiber, die ihre Beschreibung vor der Identifizierungsaussage noch mal lesen). Wiederleser wählten seltener eine Person aus der Lichtbildvorlage aus als die anderen beiden Gruppen. Dies spricht für den Ansatz der Kriteriumsverschiebung (Clare & Lewandowsky, 2004). In Experiment 2 wurden subjektive Sicherheit, Entscheidungszeit und selbstberichtete Entscheidungsprozesse als Beurteilungsvariablen der Identifizierungsleistung untersucht. Die Verwendung einer Entscheidungsregel, die schnelle und sichere Wähler zusammenfasste, führte zu mehr korrekten Klassifizierungen als jede der beiden Variablen für sich genommen. Unerwarteterweise standen selbstberichtete Entscheidungsprozesse weder für Wähler noch für Nichtwähler mit der Identifizierungsleistung in Zusammenhang. In Experiment 3 wurden subjektive Sicherheit, Entscheidungszeit und Erinnern-Wissen-Vertraut-sein-Urteile (EWV) als Beurteilungsvariablen der Identifizierungsleistung in einer Feldstudie mit zehn Zielpersonen und einer sehr großen Stichprobe evaluiert. Schnelle und sichere Wähler lagen in ihrer Entscheidung sehr häufig richtig. Die zusätzliche Verwendung des EWV-Urteils führte nicht zu einer höheren Rate korrekter Klassifizierungen. Die von den Probanden geschätzte Entscheidungszeit erwies sich ebenfalls als Beurteilungsvariable der Identifizierungsleistung. Die Beurteilung der Identifizierungsleistung von Nichtwählern durch deren Aufteilung in drei homogene Gruppen gelang nicht. Es zeigten sich jedoch Unterschiede bei der subjektiven Sicherheit und der Entscheidungszeit. Experiment 4 untersuchte den Nutzen multipler Lichtbildvorlagen (Portrait, Körper, Tasche und Profil) zur Beurteilung von Identifizierungsaussagen für neun unterschiedliche Zielpersonen. Die Identifizierungsleistungen in den vier unterschiedlichen Lichtbildvorlagen standen nicht miteinander in Zusammenhang. Dies spricht dafür, dass multiple Lichtbildvorlagen als voneinander unabhängige Beweisstücke verwendet werden können. Im Vergleich zu Wahlen eines Distraktors und Zurückweisungen besaßen Wahlen der Zielperson/des Verdächtigen einen höheren diagnostischen Wert. Die Portrait-Vorlage allein sowie dessen Kombination mit der Körper-Vorlage wiesen bezüglich Wahlen der Zielperson/des Verdächtigen die höchste Diagnostizität auf. Zusammenfassend kann aufgrund der vorliegenden Daten geschlossen werden, dass sowohl Entscheidungszeit als auch subjektive Sicherheit bei der Identifizierung erhoben und zur Beurteilung der Identifizierungsaussage miteinander kombiniert werden sollten. Ermittlungsbeamte sollten sich allerdings dessen bewusst sein, dass für Nichtwähler keine Aussage aufgrund dieser Variablen getroffen werden kann. Weiterhin scheint es keinen negativen Effekt von Personenbeschreibungen auf die Identifizierungsleistung zu geben, wenn zwischen Beschreibung und Identifizierung ausreichend Zeit liegt. Dies ist in der Realität der Fall. Die Daten sprechen weiterhin für die Anwendung multipler Lichtbildvorlagen bezüglich Wahlen der Zielperson/des Verdächtigen, um falsche Identifizierungen zu vermeiden. Hinsichtlich Distraktor-Wahlen und Zurückweisungen hingegen scheinen multiple Lichtbildvorlagen weniger brauchbar zu sein. Zukünftige Studien sollten untersuchen, wie viele und welche spezifischen Lichtbildvorlagen zu verwenden sind. In realen Fällen könnten die Ergebnisse bezüglich der hier untersuchten Beurteilungsvariablen (subjektive Sicherheit, Entscheidungszeit, Entscheidungsprozesse) und Kontrollvariablen (Personenbeschreibung, multiple Lichtbildvorlagen) von jenen, die wir in Labor- oder Feldstudien erhalten, abweichen. Gründe hierfür könnten beispielsweise die Konsequenzen der Entscheidung oder Stress bei der Enkodierung/dem Wiedererkennen sein. Es wäre interessant, Daten in realen Fällen zu erheben, so dass diese mit Feld-/Laboruntersuchungen verglichen werden könnten. Zweifelsohne wäre es ein großer Beitrag zur Identifizierungsforschung, wenn Daten auch dann erhoben werden würden, wenn DNA Spuren vorliegen, so dass die Identifizierungsleistung in realen Fällen überprüft werden könnte.
Woher wissen Augenzeugen was sie wissen?
Keywords: Personenidentifizierung; Beurteilungsvariablen; multiple Gegenüberstellungen; subjektive Sicherheit; Entscheidungszeit; person identification; postdicting identification accuracy; multiple lineups; decision times; confidence; ddc:150